2014
DOI: 10.1002/2013jd020068
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of hot air plasmas related to lightning discharges: 2. Electrodynamics

Abstract: In this paper, we develop a model of electrical discharge in air for the simulation of some of the electrical processes involved in lightning discharges, as in lightning return strokes and dart leaders. The discharge is initiated by a vertical electrical field and modeled using a nonlinear R-L-C circuit model, with which we attempt to simulate initiation, growth, radial expansion, and decay of electrical discharges related to lightning. This gas dynamic type model includes also both detailed air chemistry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Recently, Cooray and Rakov [] have shown that the upper limit of the peak current of first return strokes in negative lightning discharge is around 300 kA in the temperate region and 450–500 kA in the tropics. Such high currents could well lead to temperatures higher than a few hundred of thousands Kelvin according to the simulations made here and in the second part of this article [ Ripoll et al , ].…”
Section: Axisymmetric Radiative Shocks In Airmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, Cooray and Rakov [] have shown that the upper limit of the peak current of first return strokes in negative lightning discharge is around 300 kA in the temperate region and 450–500 kA in the tropics. Such high currents could well lead to temperatures higher than a few hundred of thousands Kelvin according to the simulations made here and in the second part of this article [ Ripoll et al , ].…”
Section: Axisymmetric Radiative Shocks In Airmentioning
confidence: 81%
“…This could be a limitation of our model, in particular at early times when the discharge develops [cf. Ripoll et al ., ]. The chemistry detail and algorithm are discussed in .…”
Section: Gas Dynamicsmentioning
confidence: 96%
See 3 more Smart Citations